Preparation of polydopamine-coated graphene oxide/Fe3O4 imprinted nanoparticles for selective removal of fluoroquinolone antibiotics in water - Feng Tan (Nature Portfolio, 2017)
Abstract Antibiotics in water have recently caused increasing concerns for public health and ecological environments. In this work, we demonstrated polydopamine-coated graphene oxide/Fe3O4 (PDA@GO/Fe3O4) imprinted nanoparticles coupled with magnetic separation for fast and selective removal of fluoroquinolone antibiotics in water. The nanoparticles were prepared by the self-polymerization of dopamine using sarafloxacin as a template. The imprinted PDA film of 10~20 nm uniformly covered the surface of GO/Fe3O4 providing selective binding sites. The nanoparticles showed rapid binding and a large capacity (70.9 mg/g). The adsorption data fitted well the Langmuir and pseudo-second order kinetic equations. The nanoparticles could be easily separated by a magnet following the adsorption and then regenerated by simple washing for repetitive adsorptions. The nanoparticles were successfully used for the removal of fluoroquinolone antibiotics in seawater, with removal efficiencies of more than 95%. The proposed strategy has potentials for efficient removal of antibiotics in environmental water.